Teacher's Strategy in Implementing Responsible Character Education in Post-Pandemic Learning at SDN Banjardowo 1 Kabuh - Hadi Saptiono; Fitri Umardiyah; Wisnu Siwi Satiti; M Farid Nasrulloh (SCHOOLAR: Social and Literature Study in Education, 2022)
Noble morality is the main foundation in the formation of akhlaqul karimah character. In order to form a person with noble character, it is very important to make efforts from an early age in the form of cultivating good character. As the Covid 19 case decreased, offline learning in class was restarted. However, there is a change in the character of students who were previously used to studying at home and then return to class The method used in this research is qualitative research. The research subject were the principal and teacher. Data collection techniques is questionnaire, interviews and documentation. The data were analyzed using a deductive method, that is data reduction; data presentation; and conclusion. Based on the results of questionnaire and interviews, the problem that is often faced by teachers is the lack of responsibility of students in doing assignments given online. As face-to-face learning resumes, teachers must implement strategies so that students can reflect the character of responsibility. the strategy used by the teacher is monitoring through a group of parents, classroom learning is designed to be more interesting and interactive, using learning applications so that material is presented through video animations, assignments are presented through the Quizizz application, insert character education in every learning process.